Can the appropriateness of eye care be measured through cross-sectional retrospective patient record review in eye care practices in Australia? The iCareTrack feasibility study. Issue 3 (4th March 2019) - Ho, Kam Chun; Rahardjo, Dian; Stapleton, Fiona; Wiles, Louise; Hibbert, Peter D; White, Andrew J R; Hayen, Andrew; Jalbert, Isabelle
Abstract : Objectives: The CareTrack study found that a wide range of appropriateness of care (ie, care in line with evidence-based or consensus-based guidelines) was delivered across many health conditions in Australia. This study therefore aimed to demonstrate the feasibility of using the CareTrack method (a retrospective onsite record review) to measure the appropriateness of eye care delivery. Design: Cross-sectional feasibility study. Setting and participants: Two hundred and thirteen patient records randomly selected from eight optometry and ophthalmology practices in Australia, selected through a combination of convenience and maximum variation sampling. Methods: Retrospective record review designed to assess the alignment between eye care delivered and 93 clinical indicators (Delphi method involving 11 experts) extracted from evidence-based clinical practice guidelines. Primary outcome measure: Number of eligible patient records, sampling rates and data collection time. This feasibility study also tested the ability of 93 clinical indicators to measure percentage appropriate eye care for preventative, glaucoma and diabetic eye care. A secondary outcome was the percentage of practitioner–patient encounters at which appropriate eye care was received. Results: A median of 20 records (range 9 to 63) per practice were reviewed. Data collection time ranged from 3 to 5.5 hours (median 3.5). The most effective sampling strategy involved random letter generation followed by sequential sampling. The appropriateness of care was 69% (95% CI 67% to 70%) for preventative eye care, 60% (95% CI 56% to 58%) for glaucoma and 63% (95% CI 57% to 69%) for diabetic eye care. Conclusions: Appropriateness of eye care can be measured effectively using retrospective record review of eye care practices and consensus-based care indicators.